Ultrasound-guided percutaneous portal transplantation of peripheral blood monocytes in patients with liver cirrhosis - Yu, Su Jong; Yoon, Jung-Hwan; Kim, Won; Lee, Jeong Min; Lee, Yun Bin; Cho, Yuri; Lee, Dong Hyeon; Lee, Minjong; Yoo, Jeong-Ju; Cho, Eun Ju; Lee, Jeong-Hoon; Kim, Yoon Jun; et al. (The Korean journal of internal medicine, 2017)
Liver transplantation offers the only definite cure for cirrhosis but lacking donors is problem. Stem cell therapy is attractive in this setting. In this study, we aimed to explore the safety and efficacy of ultrasound-guided percutaneous portal transplantation of peripheral blood monocyte cell (PBMC) in cirrhotic patients. A total of nine decompensated cirrhotic patients were randomized into three groups: group 1 (n = 3) was control group, group 2 (n = 3) received granulocyte-colony stimulating factor (G-CSF) mobilization for 3 days, and group 3 (n = 3) received G-CSF mobilized PBMCs by leukapheresis and PBMC transplantation through ultrasound-guided percutaneous portal vein puncture. Liver function and clinical features were evaluated. At baseline, the Child-Turcotte-Pugh and the model for end-stage liver disease scores were comparable in study groups. Compared with group 1, there was a tendency to improve liver function in group 3 at 6 months after treatment. Treatment was tolerable and no complications were encountered related to the G-CSF mobilization or percutaneous portal administration of PBMCs. Imaging studies showed patent portal veins at the end of the study period. Autologous PBMC transplantation through ultrasound-guided percutaneous portal vein puncture could be considered as a safe alternative treatment for decompensated cirrhotic patients.